An assessment on the role of cost and management innovations in creating and sustaining competitive advantage: case of Jet Stores - Mashayangombe, Shallome (Midlands State University, 2018)
This research sought to investigate the Effectiveness of the role of cost and management innovations in creating and sustaining competitive advantage: Case of Jet Stores ’’. . The study was carried out as a result of the noted persistent loss of business to competitors and inability to fulfill the company’s growth strategy during the period of 2011 to 2014. The research covered a body of literature for a further exhaustive knowledge of cost and management accounting techniques that an entity may adopt to achieve competitiveness and improve performance. A population of 24 respondents to gather relevant information was adopted at Jet. Descriptive research methods were adopted during the study where questionnaires (92% successful and 8% unsuccessful) and personal interviews (80% successful and 20% unsuccessful) were used for gathering data. Based on the findings, it can be concluded that Jet applies management accounting practices which were conceptually effective but technically ineffective with the current position of the organization. The practices at Jet reflected problems in, lack of documented implementation guidelines, inadequacy of communication to staff, and lack of raw materials and working capital challenges are affecting the implementation of management accounting. The researcher recommended that there should be top management participation in project development, management should provide clearly defined guidelines for the implementation of management accounting and they should consider the adoption of other management accounting techniques like ABC and balanced scorecard.